Instituto Federal De São Paulo: Educação, Ciência E Tecnologia Para Quê? - Ribeiro, Marcos Natanael Faria [UNIFESP] (2017)
The intersections between education, science and technology have become increasingly intricate and complex in contemporary societies. Understanding the conception and the bases of each of these three fields, as well as the relations established between them and also their unfolding, then presents itself as an important challenge to understand central aspects of human formation. This is because, as the authors of the Critical Theory of Society have pointed out since the twentieth century, education has played a fundamental role in cultural pseudo-formation and reproduction of the current social inequalities; positivist science has been erroneously worshiped as the ultimate expression of human rationality; and the unbridled technological advance seems to dictate the reified rhythm of today's societies. In this context, it is necessary to investigate institutions that are directly involved in the development of these three fields (isolated or jointly) in order to establish a permanent criticism that instigates reflection on the contradictory and regressive elements involved in the idea of progress frequently fomented by the education, by the science and by the technology. This dissertation aimed to investigate the foundations and concepts presented in the main documents that guide the performance of the Federal Institute of Education, Science and Technology of São Paulo (IFSP), presenting and discussing the institutional understanding regarding the triad that bases its actions, which are: education, science and technology. It also aimed to study how the academic community of one of the IFSP campuses understands the treatment given by the IFSP to the terms focused on this research, and their interrelations, within the institutional framework surveyed. The justification for this study is based primarily on the diagnosis of industrial and technological societies of the twentieth century carried out, especially, by theorists such as Theodor W. Adorno, Max Horkheimer and Herbert Marcuse. Through the analysis of official documents of the IFSP and the contributions of the academic community of this institution, it was sought to explain and understand what educational, scientific and technological presuppositions guide the actions of this Institute, as well as the intentions, the purposes and manifested contradictions, and the unfoldings evoked. To do so, three of the main IFSP documents were analyzed: the Statute, the General Regiment and the current Institutional Development Plan. A questionnaire was also applied to 96 subjects members of the three segments of the academic community of the São José dos Campos campus of the IFSP. Among the questionnaires distributed, 86 were answered and returned (54 by members of the student segment; 14 by members of the teachers segment; 18 by members of the technical-administrative segment). The documentary analyzes demonstrated the preponderance, in the IFSP, of a vision of education governed by professionalization and technological teaching, with work highlighted as an educational principle. Science is dissemined as productive instance, and the empirical research is strongly oriented toward economic development of an industrial character. With regard to technology, the discourse of "social development" and progress stands out. The analysis of the answers contained in the questionnaires found abundant elements that corroborate the data found in the IFSP documents. In addition, these responses have also brought strong criticism of current institutional policy regarding the treatment of education, science and technology.